A Moral Reasoning Intervention Program for Student-Athletes - Beller, Jennifer M.; Stoll, Sharon K. (My University, 1992)
A study was conducted to assess the effects of an intense intervention program on the moral reasoning and development of intercollegiate student-athletes. The purpose of this study was to examine the effects of an experimental applied normative ethics intervention program on the moral reasoning and moral development levels of Division I university age student-athletes. One hundred and sixty-nine subjects were pre-, post-, and postpost-evaluated with the Hahm-Beller Values Choice Inventory and the Defining Issues Test. The Hahm-Beller evaluates moral reasoning in the sport context, while the DIT assesses reasoning within the social construct. Both tests have a philosophical foundation, are objectively measured and scored, and have high validity and reliability indexes. Studies using both instruments have found that the Hahm-Beller and the DIT correlate at the .82 level (Hahm, 1989; Stoll & Beller, 1991). Furthermore, the theoretical foundation of both the Hahm-Beller and the DIT is deontic ethics. Thirty-seven student-athletes were randomly selected to enroll in the two-credit course, with 132 serving as controls. This study showed that an intense "Moral Reasoning in Sport" course appeared to increase cognitive moral reasoning and development in intercollegiate student-athletes. The course was offered in the 1989-1990 academic year and counted for two NCAA degree applicable credits.
Keywords: ethics